2018
DOI: 10.1177/1069072718808798
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Vocational Identity Status Assessment (VISA) Using Chinese Technical College Students

Abstract: Developing a vocational identity is one of the most important tasks facing any adolescent, and vocational identity has become a focus of attention in career education and guidance for decades. However, few studies have been conducted on this topic in China due to a lack of relevant measures. The purpose of this study was to validate a Chinese version of the Vocational Identity Status Assessment (VISA) using 1,650 Chinese technical college students. The 30-item VISA–Chinese Version was found to have sound relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 39 publications
4
23
1
2
Order By: Relevance
“…This model was generally an adequate to good fit for the data, whereas the four alternative models (three factor, single factor, hierarchical, and bifactor) showed poor fit. This six-factor structure is aligned with the conceptualization and initial development of the VISA (Porfeli et al, 2011) and has been confirmed in samples outside of the United States (Kim et al, 2019;Lannegrand-Willems et al, 2016;Zhang et al, 2019). Additionally, none of the other models showed adequate fit for the data.…”
Section: Summary Of Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…This model was generally an adequate to good fit for the data, whereas the four alternative models (three factor, single factor, hierarchical, and bifactor) showed poor fit. This six-factor structure is aligned with the conceptualization and initial development of the VISA (Porfeli et al, 2011) and has been confirmed in samples outside of the United States (Kim et al, 2019;Lannegrand-Willems et al, 2016;Zhang et al, 2019). Additionally, none of the other models showed adequate fit for the data.…”
Section: Summary Of Resultssupporting
confidence: 59%
“…The subscale scores have shown evidence of adequate to strong reliability and validity. For example, Cronbach’s α levels for the six subscales have consistently been above .70 (e.g., Fusco et al, 2019; Porfeli et al, 2011; Zhang et al, 2019). The six-factor structure has been shown to be invariant at the metric level across American high school and college students (Porfeli et al, 2011) and at the partial scalar level across American and Korean college students (Kim et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations